Thermal Management and Dynamic Performance of a Cooler Design for the Supercritical CO2 Turbine Shaft Cooling - Li, Jun; Gurgenci, Hal; Guan, Zhiqiang; Li, Jishun; Xue, Yujun; Li, Lun (Frontiers in Energy Research, 2022)
This paper presents the results of a numerical study on a supercritical CO2 (SCO2) turboshaft cooling device by considering heat transfer and hydrodynamics. A micro-cooling device with a radius clearance of 50 micron and a nozzle diameter of 4 mm was designed and used to investigate the heat transfer characteristics of a micro-spacing impinging and gas film dynamics. Sixteen nozzles (N = 16) are equally spaced around the shaft in single or double rows. Investigations include journal speed- and eccentricity-dependent forward and cross-coupled force coefficients, and the effects of nozzle layouts and mass flow rate on the heat transfer efficiency. Analysis of the correlation coefficient shows that the gas density in the radial clearance is the dominant factor affecting the convective heat transfer performance, while the fluid velocity is a secondary factor. And the cooling efficiency (mass flow utilization rate) at low cooling pressure (ps < 0.7 MPa) is significantly greater than that at high cooling pressure (ps > 0.7 MP). In addition, considering the structure alone, a dual-row cooler exhibits a higher average Nusselt number, also registers a higher mass flow rate at the same pressure. Once the shaft is heated only one end, the difference in effectiveness between single- and dual-row cooling is not significant, so coolers with a single-row configuration should be preferred. Then, experimental values for the temperature of the heated rotor are provided under specific cooling airflow conditions. Dynamic analysis results show that the force coefficient of the single-row configuration is more dependent on the journal rotation speed and eccentricity ratio, and exhibits a negative direct stiffness coefficient at higher inlet pressure and journal rotation speed. Moreover, cross-coupled terms (stiffness coefficient) generally have a more explicit variation tendency than direct terms, and are more sensitive to changes in shaft speed and eccentricity. Comparing the gas force coefficients of different journal speeds reveals a drastic increase in the effect of hydrodynamic pressure when the journal is eccentric. The cooler may be considered for operation with compliant support (such as bump foil) to generate additional damping and appropriately compensate for the eccentricity of the rotor.